2021
DOI: 10.1111/jdv.17228
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 pandemic and autoimmune bullous diseases: a cross‐sectional study of the International Pemphigus and Pemphigoid Foundation

Abstract: the eyelid dermatitis in parallel with respiratory improvement strongly suggests an association between skin manifestations and COVID-19. However, vitamin supplements (especially vitamin C) can also bring partial benefit in the setting of capillaritis and small-vessel dysfunction. 10 The present report gives a new insight into COVID-19-associated cutaneous findings and can therefore help clinicians in identifying early signs of the disease. In fact, the great variability of COVID-19-related dermatological di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…At present, 11 relevant studies reported prevalence data on SARS-CoV-2 infection in AIBD patients, with a pooled total of 10,060 patients (Table 1). COVID-19 symptoms were observed in 256 patients (2.5%), of whom 162 (1.6%) had a confirmed diagnosis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (Table 1). In order to compare prevalence data between AIBD patients and the general population, two recent studies performed a standardization by age, gender, country, or region of interest and period involved (12,13).…”
Section: Prevalence Of Covid-19 In Aibds Patientsmentioning
confidence: 99%
“…At present, 11 relevant studies reported prevalence data on SARS-CoV-2 infection in AIBD patients, with a pooled total of 10,060 patients (Table 1). COVID-19 symptoms were observed in 256 patients (2.5%), of whom 162 (1.6%) had a confirmed diagnosis (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (Table 1). In order to compare prevalence data between AIBD patients and the general population, two recent studies performed a standardization by age, gender, country, or region of interest and period involved (12,13).…”
Section: Prevalence Of Covid-19 In Aibds Patientsmentioning
confidence: 99%
“…Along with its clinical impact, the COVID-19 pandemic has adversely affected the emotional and mental wellbeing of patients with AIBDs. In our cross-sectional study, we could demonstrate a negative impact of the COVID-19 outbreak, including associated outdoor activity restriction and income loss, on health outcomes such as disease deterioration, stress, anxiety, and depression [ 16 ]. Fortunately, telehealth services improved the quality of care, reduced barriers (as lock-down), and allowed dermatologists to follow-up patients with chronic autoimmune dermatoses including AIBDs during the COVID-19 emergency [ 17 ].…”
Section: Further Aspects Of the Impact Of The Covid-19 Pandemic On Pa...mentioning
confidence: 99%
“…Dear Editor , Patients with autoimmune bullous diseases (AIBDs) have faced considerable challenges during the COVID‐19 outbreak 1 . SARS‐CoV‐2 vaccines became an important public health solution, but the pandemic raised awareness of vaccine hesitancy 2 .…”
Section: Figurementioning
confidence: 99%
“…DEAR EDITOR, Patients with autoimmune bullous diseases (AIBDs) have faced considerable challenges during the COVID-19 outbreak. 1 SARS-CoV-2 vaccines became an important public health solution, but the pandemic raised awareness of vaccine hesitancy. 2 We aimed to investigate the currently unknown general vaccination status among patients with AIBDs to better inform vaccine practices in this cohort of patients with potentially life-threatening inflammatory disorders.…”
mentioning
confidence: 99%